An improved approach for computation of stress intensity factors using the finite element method. (June 2019) - Liao, Minmao; Zhang, Pan
Highlights: An improved approach using the FEM for computation of SIFs is formulated. The approach results in regular meshes. The approach produces high-precision SIFs. Computed SIFs are not sensitive to the size of the complementary energy subregion. Abstract: An improved approach using the finite element method is proposed for computation of stress intensity factors. The approach is based on a subregion generalized variational principle that divides an entire cracked region into two subregions, a complementary energy subregion around a crack tip and a potential energy subregion for the rest. Finite elements are employed in the potential energy subregion. A rectangular complementary energy subregion, instead of the previous circular one, is constructed for the purpose of a regular mesh. The improved approach is reformulated and validated by four classic numerical examples. Effects of involved parameters on accuracy of the approach are investigated thoroughly. Their optimal values are recommended accordingly.